Visual search in spatial neglect studied with a preview paradigm - Fellrath, Julia; Blanche-Durbec, Vanessa; Schnider, Armin; Jacquemoud, Anne-Sophie; Ptak, Radek (Frontiers in Human Neuroscience, 2012)
Impaired visual search is a hallmark of spatial neglect. When searching for a unique feature (e.g., colour) neglect patients often show only slight visual field asymmetries. In contrast, when the target is defined by a combination of features (e.g., colour and form) they exhibit a severe deficit of contralesional search. This finding suggests a selective impairment of the serial deployment of spatial attention. Here, we examined this deficit with a preview paradigm. Neglect patients searched for a target defined by the conjunction of shape and colour, presented together with varying numbers of distracters. The presentation time was varied such that on some trials participants previewed the target together with same-shape/different-colour distracters, for 300 or 600 ms prior to the appearance of additional different-shape/same-colour distracters. On the remaining trials the target and all distracters were shown simultaneously. Healthy participants exhibited a serial search strategy only when all items were presented simultaneously, whereas in both preview conditions a pop-out effect was observed. Neglect patients showed a similar pattern when the target was presented in the right hemifield. In contrast, when searching for a target in the left hemifield they showed serial search in the no-preview condition, as well as with a preview of 300 ms, and partly even at 600 ms. The failure to fully benefit from item preview was independent of explicit judgments of simultaneity. We conclude that the visual search deficit in neglect reflects two additive factors: a biased representation of attentional priority in favour of ipsilesional information and exaggerated capture of attention by ipsilesional abrupt onsets.